Inflation and Treasury Convenience - Cieślak, Anna,Li, Wenhao,Pflueger, Carolin E. (National Bureau of Economic Research, 2024)
Using a century of data, we show that Treasury convenience yield and inflation comove positively during the inflationary 1970s-1980s, but negatively pre-WWII and post-2000. An inflation decomposition reveals that higher supply inflation predicts higher convenience, while lower demand inflation follows higher convenience. In our model, inflationary cost-push shocks raise the opportunity cost of holding money and money-like assets, inducing higher convenience, as in 1970s-1980s. Conversely, liquidity demand shocks drive up convenience but lower consumption demand and inflation in the model, as pre-WWII and post-2000. By linking the evidence to macroeconomic drivers, our results challenge the notion that inflation directly depresses Treasury convenience
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Staatspapier; Öffentliche Anleihe; Inflation; Finanzkrise; Risikoprämie; Rendite; Geldpolitik; Anlageverhalten; USA; convenience yield; Financial Markets and the Macroeconomy; Central Banks and Their Policies; Financial Crises; Government Policy and Regulation